Cytotoxicity evaluation of combined Piper betle-bioactive glass on dental pulp stem cells - Allosias, Jacqueline Ann; Noor, Siti Noor Fazliah Mohd; Luddin, Norhayati; Ghani, Huwaina Abd (Program Studi Magister Kesehatan Masyarakat Universitas Prima Indonesia, 2025)
Recent advances in dentistry emphasize the use of synthetic and natural bioactive materials for regenerating the dentine-pulp complex. This study assesses the cytotoxic effects of Piper betle-conditioned media, alone and combined with bioactive glass 45S5 Bioglass. Three test groups were used: Piper betle-only, Bioactive glass-only, and the combined Piper betle-Bioactive glass. Cytotoxicity was measured using the MTT assay on dental pulp stem cells on day one, two, four, seven, and fourteen. Cells exposed to 4.00 mg/ml Bioactive glass-only showed the highest cell viability, while Piper betle-only demonstrated the highest viability at a concentration of 31.25 µg/ml. The combined Piper betle-Bioactive glass showed the best results at 4 mg/ml and 30 µg/ml. Overall, the combination group had the highest cell viability, followed by the Bioactive glass-only and Piper betle-only groups. No significant differences were found between the combination and Bioactive glass-only groups, but significant differences existed between the combination and Piper betle-only groups. In conclusion, the combination of Piper betle and Bioactive glass enhances dental pulp stem cell proliferation, warranting further investigation into its regenerative potential.